Protocol for a pilot randomised controlled trial of zoledronic acid to prevent bone loss following sleeve gastrectomy surgery - Laura E Flores; Lynn Mack; Christopher Wichman; Ashley A Weaver; Vishal Kothari; Laura D Bilek (BMJ Open)
Introduction Sleeve gastrectomy (SG) is an increasingly used and effective treatment for obesity; however, the rapid weight loss associated with SG adversely affects bone metabolism predisposing patients to skeletal fragility. Bisphosphonate medications have been evaluated for safety and efficacy in combating bone loss in patients with osteoporosis, but their use in SG-induced bone loss is limited. The goal of this study is to investigate how a one-time infusion of zoledronic acid compares to placebo, in its ability to combat SG-associated bone loss.Methods and analysis This research protocol is a 9-month, pilot randomized controlled trial (RCT) involving 30 adult SG patients randomised to receive an infusion of either 5 mg of zoledronic acid or placebo, 6 weeks following surgery. To be included participants must be <350 lbs/158.8 kg, free of bone-impacting pathologies or medications, and must have adequate serum calcium and vitamin D levels at baseline. The primary outcome is change in areal bone mineral density (aBMD) at the total hip. Secondary outcomes include change in aBMD of the femoral neck, and lumbar spine, and change in volumetric BMD at the lumbar spine. The primary aim will be tested using a linear mixed model fit with total hip aBMD at 9 months as the outcome. Treatment, participant sex and menopausal status will be considered in analysis. Groups will be compared using contrast statements at 9 months, with change over 9 months being the primary comparison.Ethics and dissemination This study was approved by the Institutional Review Board of the University of Nebraska Medical Center (IRB820-19). Written consent will be obtained from participants at enrolment by trained staff. Careful and thorough explanation are used in obtainment of consent and voluntariness is emphasised throughout the trial. The findings of this study will be presented locally, nationally, and published in peer-reviewed journals. Additional details will be reported on ClinicalTrials.gov.Trial registration number NCT04279392